NKG2C, HLA‐E and their association with psoriasis. Issue 12 (December 2013) - Patel, Forum; Marusina, Alina I.; Duong, Christopher; Adamopoulos, Iannis E.; Maverakis, Emanual
Abstract Natural killer (NK) cell activation is regulated by the integration of signals from inhibitory and activating cell surface receptors. Both NKG2A and NKG2C pair with CD94 to form inhibitory and activating receptors specific for the HLA‐E‐canonical peptide complex. HLA‐E is a non‐classical MHC class Ib molecule with limited polymorphism. It preferentially binds to and presents leader sequence peptides derived from classical MHC class I molecules. Wilson et al. have identified an association between NKG2C deficiency and psoriasis. They have also discovered an HLA‐C‐dependent association between HLA‐E and psoriasis. Their research highlights the importance of NK cells in the pathophysiology of psoriasis. Herein, we propose two different models to explain the association between NKG2C, HLA‐E and psoriasis. In the first model, we hypothesize that NKG2C deficiency and/or HLA‐E O1:01 can inhibit the ability of NK cells to regulate autoreactive T cells, predisposing to psoriasis. The second model proposes that HLA‐E 01:03 can disrupt the presentation of the psoriasis‐inducing self‐determinant by HLA‐C, thereby protecting against psoriasis.